Upaya Baznas Kabupaten Banjar Dalam Mengoptimalkan Pengumpulan Zakat Pada Sektor Pertanian - Hagis Adetiana; Abdul Hafiz Sairazi (Interdisciplinary Explorations in Research Journal, 2023)
Abstract This study aims to examine the efforts of Baznas Banjar Regency in optimizing the collection of agricultural zakat in Banjar Regency. Zakat is one of the pillars of Islam that must be implemented for every Muslim. Agricultural products that have a high enough value that has reached the nishab must be issued zakat. However, in reality, there are still many farmers in Banjar Regency who do not know to whom this agricultural zakat is distributed, causing the distribution of agricultural zakat to miss the eight asnaf that must be given zakat, therefore Baznas Banjar Regency also plays a role in optimizing the collection of agricultural zakat in Banjar Regency This research uses empirical legal research, namely one type of legal research that analyzes and examines the legal behavior of individuals or communities in relation to the law and the data sources used come from primary data. Data were collected through interviews with Baznas Banjar Regency and documentation. The data were analyzed using descriptive analysis techniques. This research found that Baznas Banjar Regency optimizes the collection of agricultural zakat by using four methods, namely: 1) Socialization to the farming community of Banjar Regency, 2) Providing fertilizer assistance to farmers, 3) Cooperating with the Social Service and the Agriculture Office to reach further agricultural information in Banjar Regency, 4) Forming a Zakat Collection Unit (UPZ). Keywords: Efforts, Optimal, Collection, Agricultural Zakat, Baznas. Abstrak Penelitian ini bertujuan untuk mengkaji upaya Baznas Kabupaten Banjar dalam mengoptimalkan pengumpulan zakat pertanian pada Kabupaten Banjar. Zakat merupakan salah satu rukun Islam yang wajib dilaksanakan bagi setiap muslim. Hasil pertanian yang mempunyai nilai cukup tinggi yang sudah mencapai nishab maka wajib dikeluarkan zakatnya. Namun dalam kenyataanya pada petani masyarakat Kabupaten Banjar dalam penyaluran zakat pertaniannya masih banyak yang belum mengetahui kepada siapa zakat pertanian ini disalurkan sehingga menyebabkan penyaluran zakat pertanian ini luput pada delapan asnaf yang wajib diberikan zakatnya, maka dari itu Baznas Kabupaten Banjar juga berperan dalam mengoptimalkan pengumpulan zakat pertanian pada Kabupaten Banjar Penelitian ini menggunakan penelitian hukum empiris yaitu salah satu jenis penelitian hukum yang menganalisis dan mengkaji tentang perilaku hukum individu atau masyarakat dalam kaitannya dengan hukum dan sumber data yang digunakan berasal dari data primer. Data dikumpulkan melalui wawancara kepada pihak Baznas Kabupaten Banjar dan dokumentasi. Data dianalisis dengan menggunakan teknik analisis deskriptif. Penelitian ini menemukan Baznas Kabupaten Banjar dalam mengoptimalkan pengumpulan zakat pertanian dengan menggunakan empat cara yaitu: 1) Sosialisasi kepada masyarakat petani Kabupaten Banjar, 2) Memberikan bantuan pupuk kepada petani, 3) Bekerjasama dengan Dinas Sosial dan Dinas Pertanian aga menjangkau lebih jauh informasi pertanian pada Kabuapaten Banjar, 4) Membentuk Unit Pengumpulan Zakat (UPZ). Kata kunci : Upaya, Optimal, Pengumpulan, Zakat Pertanian, Baznas.